ANALISIS SIKAP KEPAHLAWANAN PADA BUKU CERITA BERGAMBAR PANGERAN DIPONEGORO SINGA MATARAM SEBAGAI BAHAN AJAR IPS BAGI SISWA KELAS IV SEKOLAH DASAR - Juheli, Lili; Supriatna, Encep (Didaktika, 2021)
The independence of a nation is beneficial from all the struggles of the former who have been willing to give up their souls and bodies. One of the figures of Prince Diponegoro who dared to fight in seizing indigenous rights from the Dutch. The figure of heroism needs to be exemplified to the next generation of the nation, especially 4 elementary school students who learn heroism in theme 5 sub-theme 3. To introduce this heroic attitude, teachers must add teaching materials that are packaged in an interesting way, such as using a storybook with a picture of Pangeran Diponegoro Singa Mataram by Nunik Utami. The reason for this ponder is to discover the figure of Prince Diponegoro who was appointed in the picture book of Pangeran Diponegoro Singa Mataram, to find out what kind of heroic attitude is depicted in the picture book of Pangeran Diponegoro Singa Mataram. The researcher conducted this research using the content analysis method and qualitative approach. Data collection procedures or techniques are carried out by direct analysis to find heroic attitudes contained in fragments of sentences in the picture storybook of Pangeran Diponegoro Singa Mataram. The comes about of the analysis appear that Prince Diponegoro is described as a prince who is persistent, humble, brave, responsible, and loves his homeland. The heroic attitudes found in the illustrated storybook ofÂ  Pangeran Diponegoro Singa Mataram, include being brave, being responsible, loving the homeland, and being willing to sacrifice. The results of the analysis are utilized as social studies teaching materials given to class IV SD regarding heroism.Â